Substance use patterns, sociodemographics, and health profiles of harm reduction service recipients in Burlington, Vermont - Tyler G. Erath; Rosalie LaCroix; Erin O'Keefe; Stephen T. Higgins; Richard A. Rawson (BMC, 2024)
Abstract Background Understanding current substance use practices is critical to reduce and prevent overdose deaths among individuals at increased risk including persons who use and inject drugs. Because individuals participating in harm reduction and syringe service programs are actively using drugs and vary in treatment participation, information on their current drug use and preferred drugs provides a unique window into the drug use ecology of communities that can inform future intervention services and treatment provision. Methods Between March and June 2023, 150 participants in a harm reduction program in Burlington, Vermont completed a survey examining sociodemographics; treatment and medication for opioid use disorder (MOUD) status; substance use; injection information; overdose information; and mental health, medical, and health information. Descriptive analyses assessed overall findings. Comparisons between primary drug subgroups (stimulants, opioids, stimulants-opioids) of past-three-month drug use and treatment participation were analyzed using chi-square and Fisher's exact test. Results Most participants reported being unhoused or unstable housing (80.7%) and unemployed (64.0%) or on disability (21.3%). The drug with the greatest proportion of participants reporting past three-month use was crack cocaine (83.3%). Fentanyl use was reported by 69.3% of participants and xylazine by 38.0% of participants. High rates of stimulant use were reported across all participants independent of whether stimulants were a participant's primary drug. Fentanyl, heroin, and xylazine use was less common in the stimulants subgroup compared to opioid-containing subgroups (p < .001). Current- and past-year MOUD treatment was reported by 58.0% and 77.3% of participants. Emergency rooms were the most common past-year medical treatment location (48.7%; M = 2.72 visits). Conclusions Findings indicate high rates of polysubstance use and the underrecognized effects of stimulant use among people who use drugs-including its notable and increasing role in drug-overdose deaths. Crack cocaine was the most used stimulant, a geographical difference from much of the US where methamphetamine is most common. With the increasing prevalence of fentanyl-adulterated stimulants and differences in opioid use observed between subgroups, these findings highlight the importance and necessity of harm reduction interventions (e.g., drug checking services, fentanyl test strips) and effective treatment for individuals using stimulants alongside MOUD treatment.